Determination of carotenoid content of crude palm oil extracted from different fruitlets’ layers of ripe bunches / Hameerul Hijan and Alawi Sulaiman - Hamzah, Hameerul Hijan; Sulaiman, Alawi (Faculty of Plantation and Agrotechnology, 2018)
Elates Guineensis is the major planted commodity crop in Malaysia. In the year 2017. It contributed for almost RM 72 billion to the second largest palm oil producer which is Malaysia. It can be exported to other countries to gain maximum income. However, the current processing method of producing crude palm oil will deteriorate carotene content. The objective of this study was to determine the carotenoid content of crude palm oil extracted from different fruitlets’ layers of ripe bunches. Firstly, the weeks of bunches from inflorescence was determined. Then, bunches were divided to 4 parts and take % bunches as sample. Next, put the sample into pot and boiled at least 2 hours. After boiling, fruitlets were taken out from pot and mesocarps were peeled off and then pressed. Before pressing process occurs, fruitlets were weighted. Basically, every sample of monocarp is 1 kg. Then, continue pressing until the oil came out from mesocarp. Finally, take the sample to Sime Darby Laboratory to analyze the carotene by using NIRS DAI650. It is proven that the longer the mesocarps are exposed to the sunlight, the higher its carotene content will be. The amount of carotene for the first layer is ±968.07 ppm which was greater compared to the second layer with only ±863.87 ppm. In conclusion, carotene is actually beneficial for human health because it acts like antioxidant and under developing countries really need this element to survive.